Dimensi Tubuh Sapi Friesian Holstein dan Limousin Betina Berdasarkan Morfometrik dengan Citra Digital - Hakim, A.; Nuraini, H.; Priyanto, R.; Harsi, T. (Jurnal Ilmu Produksi dan Teknologi Hasil Peternakan, 2019)
Digital image analysis have been applied to determine and follow the body measurement, live weights, and animal growth. The objectives on this study were to compare linear body measurement (BMs) method (manually and digital image analysis) and to compare size and body dimension of Friesian Holstein (FH) and Limousin cows. In this study, the BMs of FH and Limousin cows was determined using digital image analysis (IA). Linear measurement of primary morphometrics, part of Columna vertebralis, and extrimity length of cows was first determined manually, by direct measurement. Then the digital images of cows were taken and the results obtained through the calculations were recorded into the computer and analized by Corel draw. Result showed that the BMs with both methods measurement was not significant different and IA method had lower coefficient variation (CV) than manual, which indicates the IA method can be used for morphometric study. For the body dimension, FH had larger frame size and lower body weight than Limousin. The different of breed caused differences in morphometric performances. FH had longer thoraxoc vertebrae, wither height, space between ischium, and space coxae to ischium than Limousin. Limousin had longer cervicalis vertebrae, sacral vertebrae, and scapulla.